2014
DOI: 10.3109/08977194.2014.939805
|View full text |Cite
|
Sign up to set email alerts
|

Growth retardation and growth hormone deficiency in patients with Ataxia telangiectasia

Abstract: Our results show that a disturbance in the GH/IGF-1 axis was present in 58.3% of A-T patients. Low levels of GH were the result of reduced central GH secretion. GH treatment may be a therapeutic option for A-T patients with severe growth failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 43 publications
4
56
0
Order By: Relevance
“…A recent study by Voss et al demonstrated severe GH deficiency in 6/10 AT patients with growth retardation (14). The same group has previously reported low IGF-I and IGFBP3 levels in their patients, deteriorating with age (8).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…A recent study by Voss et al demonstrated severe GH deficiency in 6/10 AT patients with growth retardation (14). The same group has previously reported low IGF-I and IGFBP3 levels in their patients, deteriorating with age (8).…”
Section: Discussionmentioning
confidence: 87%
“…Our most prominent findings were growth retardation and impaired body weight. These could be attributed to oropharyngeal dysphagia, chronic pulmonary infection, and impaired glucose metabolism (14). Growth impairment preceded the impairment in weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations